Results and Performance of the World Bank Group 2012 : Volume II. Appendixes - Independent Evaluation Group (Washington, DC: World Bank, 2013)
Management welcomes the Independent Evaluation Group (IEG) report results and performance 2012 of the World Bank group (RAP) and its overall positive assessment of the World Bank group development effectiveness. Management appreciates that the report provides a balanced picture of the World Bank group activities and recognizes that all three institutions have taken important steps to strengthen results, monitoring, and reporting. The report is especially useful to management to prioritize the challenges in the context of the ongoing efforts to strengthen focus on results. Management is concerned that the share of investment lending projects rated moderately satisfactory or better appears to be declining, after a long period of improvements observed since the mid-1990s.This reports includes five chapters: (i) the global development context ;(ii) world bank group operations: findings from evaluation work; (iii) enhancing the bank group's effectiveness;(iv) strengthening institutional results orientation;(v) conclusion: areas for attention